2021
DOI: 10.1007/s00330-021-08191-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breathing state on the accuracy of automated patient positioning in thoracic CT using a 3D camera for body contour detection

Abstract: Objective To assess the influence of breathing state on the accuracy of a 3D camera for body contour detection and patient positioning in thoracic CT. Materials and methods Patients who underwent CT of the thorax with both an inspiratory and expiratory scan were prospectively included for analysis of differences in the ideal table height at different breathing states. For a subgroup, an ideal table height suggestion based on 3D camera images at both breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As compared with previous studies using a CT system equipped with a 3D camera, our proposed method demonstrated comparable or superior accuracy to that of the 3D camera system (Table 3). 9,11,13 Booij et al 12 stated that aligning the positioning using the camera system results in accurate patient positioning, if the camera image and subsequent CT scan are acquired in the same breathing state. Scout images are generally performed under the same breathing control as the scanning is, and thus, a difference in breathing state does not occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As compared with previous studies using a CT system equipped with a 3D camera, our proposed method demonstrated comparable or superior accuracy to that of the 3D camera system (Table 3). 9,11,13 Booij et al 12 stated that aligning the positioning using the camera system results in accurate patient positioning, if the camera image and subsequent CT scan are acquired in the same breathing state. Scout images are generally performed under the same breathing control as the scanning is, and thus, a difference in breathing state does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with previous studies using a CT system equipped with a 3D camera, our proposed method demonstrated comparable or superior accuracy to that of the 3D camera system (Table 3). 9,11,13 Booij et al 12 stated that aligning the positioning using the camera system results in accurate patient positioning, Figure 6 shows a case of cecal cancer in a 62-year-old man with idiopathic scoliosis. As shown in the scout and axial images, the contour of the chest to the upper abdomen was greatly deformed because of scoliosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical and depth information are processed to automatically adjust the table height to match the isocenter of the patient with the isocenter of the scanner and to support the definition of the scan range. [30][31][32][33] Manava et al 31 analyzed data from 3118 patients who underwent CT of the chest and abdomen: 1575 patients were positioned laser-guided by a radiographer, 1561 patients with 3D camera guidance. Although the radiographers were highly trained, isocenter positioning was significantly improved with the 3D camera.…”
Section: Camera-based Patient Positioningmentioning
confidence: 99%